Reliability Issues and Degradation Mechanisms of p-GaN Gated E-Mode AlGaN/GaN Power HEMTs: A Critical Review - J. Ajayan; Asisa Kumar Panigrahy; Sachidananda Sen; Maneesh Kumar; Shubham Tayal (IEEE Access)
GaN-HEMTs on silicon (Si) or SiC or sapphire substrates are growing in popularity and is expected to completely transform the power electronics industry. Although GaN HEMTs operate in D-Mode by default, E-Mode operation is necessary for ease of IC design, low power consumption and safe operation. p-GaN gated HEMTs offer a breakdown voltage (V ${}_{BR}$ ), transconductance (g ${}_{m}$ ), power added efficiency (PAE) and ON-current (I ${}_{ON}$ ) of over 2230 V, 205 mS/mm, 55.4 % and 1 A/mm, respectively, which makes them highly suitable for future RF-power switching applications. The time-dependent breakdown of the AlGaN-p-GaN/metal stack (due to avalanche multiplication) is a serious reliability concern in p-GaN HEMTs. Material defects, back gate effects, gate leakage, bias stress effects, ESD & short circuit failures, radiation effects and thermal effects are also important reliability concerns that can result in performance degradation, including current collapse, reduced breakdown voltage, increased on-resistance and device failure. Mechanisms like interface states, ion migration, and electron trapping are also crucial to the aging of p-GaN HEMTs. Understanding these reliability issues and degradation mechanisms is critical for enhancing the robustness of p-GaN HEMTs in power electronics and RF applications. Therefore, this article reviews the reliability issues and various degradation mechanisms of p-GaN gated E-Mode HEMTs such as forward/reverse bias stress effects, back gate effects, current collapse, charge trapping effects, radiation effects, short circuit (SC) & electrostatic discharge (ESD) failures and high temperature reliability issues. RON degradation, gate breakdown, PBTI and NBTI remains serious concerns in the development of p-GaN gated E-Mode HEMTs for future consumer electronics, wireless networks, industrial motors, electric vehicles and space/aeronautic applications.